Pemberian Buah Naga Merah Pada Ny. A dengan Diagnosis Hipertensi di Desa Sungai Batang Ilir Kecamatan Martapura Barat: Laporan Kasus - Agianto; Sahrawardi (Nerspedia, 2023)
Background: Hypertension can cause complications such as heart attacks, strokes and kidney disorders, so good blood pressure control is necessary. Information obtained at the Martapura Barat Health Center, hypertension is the highest disease in the 10 most diseases because people have bad habits and lifestyles, namely fond of consuming coconut milk and salted food (dried salted fish) so that it becomes a trigger factor for hypertension. Giving red dragon fruit intervention can be an alternative solution to deal with the problem of hypertension.